PENGARUH JARAK PENGEREMAN DAN KONDISI JALAN TERHADAP SUHU KAMPAS REM PADA SEPEDA MOTOR 150 CC: EFFECT OF BRAKING DISTANCE AND ROAD CONDITIONS ON BRAKE PAD TEMPERATURE ON 150 CC MOTORCYCLE - Rio, Dewandryo Putra Mahardika (Jurnal Teknik Mesin, 2022)
Road safety is the right of all road users. However, the reality is that the high number of deaths is still caused by accidents while driving on the road. One of the contributing factors to these accidents is the lack of warning signs when the braking system malfunctions. This study aims to monitor the temperature during braking and provide an early warning safety system for motorcycle riders based on the ESP32 microcontroller and the MAX6675 thermocouple type-K temperature sensor module. The method in this study, employed a quantitative experimental approach by conducting experiments on three types of road terrains: flat road, gentle downhill road, and steep downhill road. Braking was performed at intervals of 30 meters, with a final braking distance of 300 meters. The findings of this study indicate that the distance and road conditions have an impact on the increase in brake pad temperature. The experiments showed a significant temperature increase at a braking distance of 300 meters, with values of 99.75°C on flat roads, 115.50°C on gentle downhill roads, and 129.00°C on steep downhill roads.